Finite element analysis of the influence of occlusal contact on maxillary All-on-4 immediate loading under different framework materials - JIANG Nan, GU Weiping (Kouqiang yixue)
Objective To explore the occlusal contact designs in accordance with biomechanical principles in the All-on-4 immediate loading scheme of the edentulous maxilla with four kinds of framework materials. Methods Cone beam CT of an edentulous maxilla was selected. The cone beam CT data, crown, framework, abutment and implant data were used and the titanium, cobalt-chromium alloy, polyetheretherketone(PEEK) and resin framework materials were specified. The finite element models were divided into 4 groups, according to whether the anterior teeth or the cantilever had occlusal contact(AC group: both the anterior teeth and the cantilever were loaded;ANC group: load on the anterior teeth and no load on the cantilever; NAC group: no load on the anterior teeth and load on the cantilever;NANC group: no load on both the anterior teeth and the cantilever). The stress of cortical bone, implant and framework, the micromotion of implant and the deformation of framework were calculated and statistical analysis was then performed. Results Among the four types of framework materials, in terms of cortical bone peak stress, the NAC group had the highest value and the ANC group had the lowest. There was a statistical difference between the NAC group and the other three groups respectively(P<0.05). With the four framework materials, in terms of the peak stress of implant, the ANC group had the highest. When the framework material was PEEK or resin, there was a significant difference between the ANC group and the other three groups(P<0.05). The peak stress value of the framework compared, the NAC group had the highest peak stress and was significantly different from the other three groups(P<0.05). The ANC group had the lowest peak stress and was significantly different from the other three groups(P<0.05) when the framework material was titanium or cobalt-chromium alloy. If the framework material was PEEK or resin, there were no statistical differences between the four occlusal schemes. Comparing the peak micromotion of implant or the peak deformation of framework, the ANC/NAC group was significantly higher than the AC/NANC group(P<0.05). Among the different framework materials, titanium and cobalt-chromium alloy had higher peak stress of framework compared to PEEK and resin(P<0.05), with less stress transmitted to the cortical bone and implant(P<0.05). Conclusion ①In terms of occlusal contact design, when the All-on-4 immediate loading scheme is applied to the edentulous maxilla, the scheme that the anterior teeth loaded and the cantilever unloaded(ANC) is more conducive to the stress distribution of bone-implant interface. ②The application of load on both anterior teeth and cantilever(AC) or the absence of load on both anterior teeth and cantilever(NANC) is favourable for reducing the peak micromotion of implant and the peak deformation of framework. ③Among the four types of framework materials, titanium or cobalt-chromium alloy framework transmit less stress to the bone-implant interface than PEEK or resin framework.